2017
DOI: 10.1007/s00449-017-1755-5
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of microalgae derived lipids with supercritical carbon dioxide in an industrial relevant pilot plant

Abstract: Microalgae are capable of producing up to 70% w/w triglycerides with respect to their dry cell weight. Since microalgae utilize the greenhouse gas CO2, they can be cultivated on marginal lands and grow up to ten times faster than terrestrial plants, the generation of algae oils is a promising option for the development of sustainable bioprocesses, that are of interest for the chemical lubricant, cosmetic and food industry. For the first time we have carried out the optimization of supercritical carbon dioxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 15 publications
1
25
0
2
Order By: Relevance
“…In a next step, the products are extracted with an organic solvent. As an alternative, extraction with supercritical CO 2 is also developed [221][222][223][224][225]. Supercritical CO 2 extraction has several advantages: The extraction efficiency is high since the fluid density and consequently the solvent quality can be controlled by changes of pressure or temperature, it allows for low-temperature processing, is non-toxic, nonflammable, and the supercritical solvent can easily be removed [224,226,227].…”
Section: Downstream Processing and Purificationmentioning
confidence: 99%
“…In a next step, the products are extracted with an organic solvent. As an alternative, extraction with supercritical CO 2 is also developed [221][222][223][224][225]. Supercritical CO 2 extraction has several advantages: The extraction efficiency is high since the fluid density and consequently the solvent quality can be controlled by changes of pressure or temperature, it allows for low-temperature processing, is non-toxic, nonflammable, and the supercritical solvent can easily be removed [224,226,227].…”
Section: Downstream Processing and Purificationmentioning
confidence: 99%
“…Supercritical carbon dioxide (ScCO 2 ) extraction of microalgal lipids has received attention as an alternative to organic solvent extraction and has been shown to be an ideal method for extracting certain lipids [7]. Several studies reported high extraction yield using ScCO 2 [8] [9] [10]. However, from these works, it appears that the microalgae Abbreviations: SPE, solid phase extraction; PPL, phospholipids; GL, glycolipids; NL, neutral lipids; ScCO 2 , supercritical carbon dioxide ⁎ Corresponding author at: Laboratoire de Chimie Agro-industrielle (LCA), Université pretreatment is highly significant to perform an efficient extraction with ScC0 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Venturi et al [ 9 ] developed a phenol-enriched refined olive oil with its own phenolic compounds extracted from wastewater produced during physical processing in order to improve the nutraceutical value, as well as the antioxidant capacity of olive oil. On the other hand, marine sources (e.g., macroalgae, microalgae), food by-products and plant-derived natural products can be used to extract bioactive compounds, such as polyunsaturated fatty acids (PUFAs) and phenolics, among others, that are widely recognized as important nutritional components that may help prevent various cardiac disorders [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%